Exploring the effects of spanwise wing deformation on lift coefficient and trailing vortices properties at low Reynolds number. - Garrido-Martín, Manuel; Solís-García, Pedro; Durán, E.; Gutiérrez-Castillo, Paloma; Del-Pino-Peñas, Carlos Manuel (My University, 2024)
We have conducted an experimental investigation on the effect of spanwise wing deformation on the lift coefficient and the properties of the wingtip vortices generated by several NACA0012 symmetric wing models.
Keywords: Movimiento de vórtices; Aerodinámica; Wingtip vortex; Aerodynamics; Flow visualization; Wing model deformation